PENGETAHUAN ORANG TUA TENTANG PENDIDIKAN SEKS DINI PADA ANAK USIA PRA SEKOLAH (3-6 TAHUN) DI TK TUNAS JAYABANGSAL MOJOKERTO - Dyah Siwi Hety (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2017)
Parents are teachers and giving examples for their children, because a lot of knowledge that can be obtained from them. This is related to the knowledge of parents about early sex education to their children. The early sex education is still taboo, especially early sex education of preschool children, and rarely given even known parents, so this study intends to find out the knowledge of parents about early sex education to preschoolers (3-6 years).This study design using a descriptive design which aimed to identify the knowledge of parents about early sex education to preschoolers (3-6 years) in Tunas Jaya Bangsal Kindergarten Mojokerto. The variable in this study is the knowledge of parents about early sex education to preschoolers (3-6 years). The population in this study were all parents who waited for his son was totaling 67 people. Samples taken by accidental sampling method. The data collection was done by the distribution of questionnaires to the respondent, then the results were analyzed using descriptive statistics.The results of this study showed that the knowledge of parents about early sex education of preschool children (3-6 years) more than 50% is less, namely 26 respondents. Knowledge of parents about the notion of early sex education of preschool children at most is less that 16 respondents. Knowledge of parents regarding the timing of early sex education of preschool children most is not good that 14 respondents. Knowledge of parents regarding the granting of early sex education of preschool children at most was that 19 respondents.Early sex education of preschool children is very important, this is so preschoolers can develop in accordance with the level of development and gender. Knowledge of parents lacking against early sex education of preschool children partly because the level of parental education are low, and the lack of information about early sex education preschoolers. The role of parents in finding and absorbing information about early sex education preschool aged children is to increase the knowledge of parents about early sex education to preschoolers which includes among others the understanding, time of administration, and mode of administration of early sex education preschoolers.